Спротив пригніченню – право сили чи право права? - Кириченко, В.; Kyrychenko, V. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У статті досліджуються історичні корені опору гнобленню, дуальна природа цього явища: як права і як сили. Розглядаються доктринальні концепції даного феномена, історія його закріплення в позитивному праві як права на опір (jus resistendi), визнання цього права нормою міжнародного правопорядку, плюралізм підходів до його конституційного закріплення. Незважаючи на те, що право на опір отримало міжнародно-правове визнання, а кількість конституцій у світі, якими воно передбачено, перетнуло 20-відсотковий бар'єр, майже кожен аспект цього права є спірним. Більшість демократичних держав все ж не поспішає законодавчо оформити право на опір. Приділено увагу особливостям jus resistendi, які притаманні, його суб'єкту, що характеризується множинністю, цілям, а також способам реалізації зазначеного права, які неможливо закріпити в позитивному праві. The article considers the historical roots of resistance to oppression, the dual nature of this phenomenon as the right of force or the right of law. In the focus of attention are the doctrinal conceptions of the phenomenon under consideration, history of fixing it in the positive law as the right for resistance (jus resistendi), recognition of this law as international norm, pluralism of approaches to its constitutional recognition. Despite the right for resistance received international legal recognition and the number of constitutions in the world in which it is stipulated has crossed 20 percent threshold, nearly every issue of this right is controversial. Most democratic states are in no hurry to issue legally the right for resistance to oppression and moreover to overthrow the existing regime. Much attention is paid to the peculiarities of jus resistendi which is inherent, particularly to its subject, and is characterized by multiple goals, as well as methods of implementing this right, which can not be fixed in positive law. The author concentrates on the issues characterizing the peculiar perception of this phenomenon in the Eastern tradition. Much attention is paid to non-violent forms of realization of this right, and such extreme manifestation of it as revolution, the impact of communication technologies on counteraction to the authorities.
Resistance to Oppression – the Right of Force or the Right of Law?
Keywords: право на спротив пригніченню; революція; повстання; тиранія; right for resistance to oppression; revolution; rebellion; tyranny